ANALYSIS OF LEADERSHIP STYLE BY USING THE MODEL OF HERSEY AND BLANCHARD - Adi Lukman Hakim; Erna Nur Faizah; Ninik Mas'adah (Journal of Leadership in Organizations, 2021)
Introduction/Main Objectives: This research raises human resources management within the crediting bank, where employees require reliable and competent leadership. Leadership is categorized as the concept of empowering when the leader shares direction, a support system, friendly, synergizing, and providing exemplary examples to his subordinates.Background Problems: Through scientific ways, this study attempted to respond to the research questions, which are: 1) how is the maturity of employees in the Anugerah rural bank located in Purwosari, 2) what are the applications of leadership styles, duty behavior, and relationship behaviors at there, and 3) in which quadrant of leadership styles of the chief of operational, general, administrations, and marketing department? Novelty: The current study engaged four situational leadership in a model. Research Methods: The survey design administered the questionnaire, interviews, and observation to the target samples. The data, then analyzed using descriptive analysis and the range scale. Finding/Results: The operational and general divisions reflect their leadership styles in quadrant II representing a consultation or low task and relationship behavior. Besides, quadrant III, which implies a participating leadership style with high task and relationship behavior, has been practiced by the marketing department. The administrative division tends to use the leadership style from quadrant IV or delegating with high task behavior relationship. Conclusion: Leaders can select any leadership style, but they must remain aware of task and relationship behavior. This recent study has many limitations; hence, the future researcher can apply other leadership styles under different conditions.